Where Shall We Go? - Nandini Nayar (Karadi Tales company Pvt. Ltd, 2014)
Sameer has plans for the summer holidays?big plans. And he has the perfect place in mind. Can Amma guess where he wants to go? Be transported by Nandini Nayar's nimble little vignettes and Francesco Manetti's joyous locales in this quirky, fanciful tale.